Comparison of Dydrogesterone and GnRH Antagonists for Prevention of Premature LH Surge in IVF/ICSI Cycles: A Randomized Controlled Trial - Batool Hossein Rashidi; Azam Tarafdari; Seyedeh Tahereh Ghazi Mirsaeed; Ensieh Shahrokh Tehraninezhad; Fatemeh Keikha; Bita Eslami; Seyede Masoumeh Ghazi Mirsaeed; Mina Jafarabadi (Tehran University of Medical Sciences, 2020)
Objective: To compare the effect of dydrogesterone and Gonadotropin releasing hormone (GnRH) antagonists on prevention of premature luteinizing hormone (LH) surge and pregnancy outcomes in infertile women undergoing Invitro fertilization/ Intra cytoplasmic sperm injection (IVF/ICSI). Materials and methods: In a Randomized controlled trial (RCT), two-hundred eligible women undergoing in vitro fertilization (IVF) /intracytoplasmic sperm injection (ICSI) treatment were randomly assigned into two groups. Human menopausal gonadotropin (HMG) was administered for controlled ovarian stimulation (COS) in both groups. Intervention group (group 1) received 20 mg dydrogesterone from day 2 of menstrual cycle till trigger day and control group (group2) received GnRH antagonist from the day that leading follicle reached 13 mm in diameter till trigger day. Serum levels of LH, estradiol and progesterone were measured on the trigger day. The primary outcome measure was the incidence of a premature LH surge, and the secondary outcomes investigated were the chemical and clinical pregnancy rates in the first FET cycles. Results: There were no significant differences in patients' age, BMI, AMH levels, previous IVF cycle, and cause of infertility between the two groups. None of the patients in two groups experienced a premature luteinizing hormone surge. The numbers of retrieved oocytes, the MII oocytes and good quality embryos, were significantly higher in the intervention group than antagonist group (p < 0.05). The overall chemical pregnancy rate in intervention group (43/91: 46.2%) and control group (45/91: 49.5%) (p = 0.820) was similar. Meanwhile, the clinical pregnancy rate was similar between groups too. Conclusion: Regarding the cost, efficacy and easy usage of dydrogestrone, it may be reasonable to use it as an alternative to GnRH antagonist for the prevention of premature LH surge.